Sustainable Skincare Innovation: Cork Powder Extracts as Active Ingredients for Skin Aging - Ana Silva; Cláudia Pinto; Sara Cravo; Sandra Mota; Liliana Rego; Smeera Ratanji; Clara Quintas; Joana Rocha e Silva; Carlos Afonso; Maria Elizabeth Tiritan; Honorina Cidade; Teresa Cruz; et al. (Pharmaceuticals)
Background: An emerging practice within the concept of circular beauty involves the upcycling of agro-industrial by-products. Cork processing, for instance, yields by-products like cork powder, which presents an opportunity to create value-added cosmetic ingredients. Building upon our previous research, demonstrating the antioxidant potential of hydroalcoholic extracts derived from two distinct cork powders (P0 and P1), in this work, aqueous extracts were prepared and analyzed. The safety and bioactivities of the newly obtained aqueous extracts, as well as the 30% ethanol extracts, previously reported to be the most promising for skin application, were also evaluated. Methods: Aqueous extracts were obtained from cork powders (P0 and P1) and the identification and quantification of some polyphenols was achieved by liquid chromatography (LC). Antioxidant potential was screened by DPPH method and the bioactivity and safety of extracts were further explored using cell-based assays. Results: All extracts exhibited a reduction in age-related markers, including senescence-associated beta-galactosidase (SA-β-gal) activity. Additionally, they demonstrated a pronounced anti-inflammatory effect by suppressing the production of several pro-inflammatory mediators in macrophages upon lipopolysaccharide stimulation. Moreover, the extracts upregulated genes and proteins associated with antioxidant activity, such as heme oxygenase 1. The aqueous extract from P1 powder was especially active in reducing pro-inflammatory mediators, namely the Nos2 gene, inducible nitric oxide protein levels, and nitric oxide production. Moreover, it did not induce skin irritation, as assessed by the EpiSkin test, in compliance with the OECD Test Guidelines. Conclusions: Overall, our findings underscore the potential of aqueous extracts derived from cork waste streams to mitigate various hallmarks of skin aging, including senescence and inflammaging, and their suitability for incorporation into cosmetics formulations. These results warrant further exploration for their application in the pharmaceutical and cosmetic industries and could foster a sustainable and circular bioeconomy.